Acorn (Quercus spp.) fruit lipids: Saponifiable and unsaponifiable fractions: A detailed study - León-Camacho, Manuel; Viera-Alcaide, Isabel; Vicario, Isabel M. (Journal of the American Oil Chemists' Society, 2004)
The composition of the oils extracted from the acorn fruit of three species of Mediterranean oaks, Quercus ilex L., Q. suber L., and Q. faginea L., was characterized. Both major and minor components, including FA, TG, sterols, methyl sterols, triterpenic and aliphatic alcohols, tocopherols, and hydrocarbons, were identiﬁed by standard methods and MS. Highresolution GLC and HPLC were used for quantiﬁcation. The FA profile, together with the equivalent carbon numbers and TG carbon numbers, was compared with data for other edible vegetable oils. Oil yield, expressed as wet weight, was 5% (w/w). Sterol content was remarkable for the three species (8,563–11,420 mg/kg), with β-sitosterol being the most abundant (80%). Oils were also high in tocopherol, with a wide variation between species (165–456 mg/kg) but with γ-tocopherol predominating in all three oils (90% of the total tocopherol content). Also, high terpenic alcohol contents were found (1527–2984 mg/kg), with dammaradienol and β-amyrin being the most abundant (33–60% of the total alcohol content). Bioactive properties and industrial applications of this underutilized native product are also discussed.
Keywords: Acorn oil; fatty acid; hydrocarbons; Quercus spp.; sterols; triglycerides